3-DIMENSIONS OF INTERACTIVE MULTIMEDIA VALIDITY TO INCREASE VISUAL-SPATIAL INTELLIGENCE IN MOLECULAR GEOMETRY - Abdul Aziz Tamami; Kusumawati Dwiningsih (Universitas Negeri Yogyakarta, 2020)
The research aimed to find out the properness of the 3-dimensions (3D) interactive multimedia as the learning media to increase student’s visuospatial intelligence in molecular geometry. This research and development used design of 4D by Thiagarajan that was modified by Ibrahim. Modified design implemented until third step (development phase). The research subject was 10th-grade students that were getting molecule shapes geometry sub-matter. The 3D interactive multimedia was declared as valid based on the expert judgement through validation process by three validators consisting of 2 lecturers and 1 chemistry teacher. The content and construct validity sheet are used as an instrument on the validation process. Multimedia validity can be avowed from content validity and construct validity. The content validity was determined by the content standard and content systematic criteria including usefulness in promoting students’ visuospatial intelligence. The construct validity was determined by software techniques and visual communication. Validation result data was used quantitative descriptive analysis. According to the validation result, the content and construct validity percentage results as 81% and 84% at the more valid category, so that 3D interactive multimedia can be declared valid as a learning media. The media will be useful to improve the learning quality.